Imperative mandate AS A FORM OF RELATIONSHIP AND DEPUTY OF VOTERS - Задорожня, Г. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In the article an author explores legislative bases of strengthening of legal interconnection of deputy and electors, analyses the necessity of strengthening of responsibility of folk representative before the people of Ukrain.